DIVERSIFIKASI PANGAN BERBASIS POTENSI LOKAL SEBAGAI STRATEGI KETAHANAN PANGAN KELUARGA DI KEPULAUAN SOP, KOTA SORONG - Leiwakabessy, Ivonne (SOLIDEO Jurnal Pengabdian Masyarakat, 2025)
Food security encompasses both national and household levels. The high dependence of Indonesian society on rice poses a major challenge, making local potential-based food diversification essential. The Sop Islands of Sorong City possess abundant local food resources, particularly cassava, yet their utilization remains limited. This community service program aimed to raise awareness of food diversification, train skills in processing cassava into croquettes, and promote the development of local food-based micro-enterprises. A participatory approach was applied through socialization, training, demonstrations, and technical assistance. The results indicated improved community knowledge on food diversification, enhanced ability to produce cassava croquettes, and the product’s potential as both an alternative food and a household business opportunity.